Association between obesity and triple-negative breast cancer: a systematic qualitative review - Iervolino, Luiz Lerario; de Moraes, Sérgio Rodrigues; Filassi, José Roberto; Baracat, Edmund Chada; Masili-Oku, Sérgio (Mastology, 2024)
Introduction: The relation between obesity and triple-negative breast cancer (TNBC) is not totally elucidated. TNBC represents a heterogeneous group of aggressive growth neoplasms. The concepts related to the development of hormone receptor-positive tumors cannot be directly extended to this group. To evaluate the association between obesity and TNBC, considering as primary outcome the assessment of the incidence of this tumor subtype in this population and as secondary outcomes the specific pathophysiology, prognosis, and treatment in this context. Methods: This was a systematic review following the Preferred Reporting Items for Systematic reviews and Meta-Analyses — PRISMA statement. PubMed/MEDLINE and Cochrane were the databases used as primary paper sources. Inclusion according to titles and abstracts allowed a secondary selection by reference list revision. The final full-text review was done on the most opportune studies identified. Results: A total of 52 articles were included. Epidemiology: A higher frequency of obesity among TNBC patients compared to other subtypes and TNBC in obese women was observed in the literature. It is uncertain whether premenopausal status is an aggravating factor. Pathophysiology: Several studies identified the production of different factors by obese adipose tissue and their regulation of genes related to the expression of stem-like cell properties, mainly leptin, IL-6, and IL-8. Prognosis: Most studies pointed out that disease-free survival and overall survival are independent of body mass index. Treatment: Weight reduction showed no significant power in improving prognosis but may favor primary incidence prevention. Drugs based on obesity-related pathways are still in research, and various potential targets were raised. Conclusions: Obesity is a risk factor for TNBC. Obese-related inflammatory cytokines may contribute to tumor development. Once TNBC is established, the prognosis does not differ according to initial body mass index changes. No target drug for obesity-related tumorigenic pathways is currently available for clinical use.